Multiple Measures of Fixation on Social Content in Infancy: Evidence for a Single Social Cognitive Construct?. (22nd September 2015) - Gillespie‐Smith, Karri; Boardman, James P.; Murray, Ian C.; Norman, Jane E.; O'Hare, Anne; Fletcher‐Watson, Sue
Abstract : The preference of infants to fixate on social information in a stimulus is well known. We examine how this preference manifests across a series of free‐viewing tasks using different stimulus types. Participants were thirty typically developing infants. We measured eye movements when viewing isolated faces, faces alongside objects in a grid, and faces naturally presented in photographed scenes. In each task, infants fixated social content for longer than nonsocial content. Social preference scores representing distribution of fixation to social versus general image content were highly correlated and thus combined into a single composite measure, which was independent of demographic and behavioral measures. We infer that multiple eye‐tracking tasks can be used to generate a composite measure of social preference in infancy. This approach may prove useful in the early characterization of developmental disabilities.